2017
DOI: 10.1016/j.bmc.2017.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate inhibits bacterial virulence and invasion of host cells

Abstract: Increasing antibiotic resistance and beneficial effects of host microbiota has motivated the search for anti-infective agents that attenuate bacterial virulence rather than growth. For example, we discovered that specific flavonoids such as baicalein and quercetin from traditional medicinal plant extracts could attenuate Salmonella enterica serovar Typhimurium type III protein secretion and invasion of host cells. Here, we show epigallocatechin-3-gallate from green tea extracts also inhibits the activity of S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Both activities are mainly due to the presence of polyphenols, the most abundant of which are the catechins, particularly epigallocatechin gallate (EGCG), which represents 50–80% of the total catechin content (Khan and Mukhtar, 2007). The reported antimicrobial activity of EGCG against human pathogens (Osterburg et al, 2009; Gordon and Wareham, 2010; Liu et al, 2017) may involve the direct disruption of bacterial membrane integrity (Lee et al, 2009), as well as indirect effects such as the chelation of iron (Hider et al, 2001), the inhibition of folate biosynthesis (Navarro-Martínez et al, 2005) and the inhibition of virulence functions such as type III secretion systems or quorum sensing (Spina et al, 2008; Yin et al, 2015; Tsou et al, 2017). In particular, interference with quorum sensing may affect density-dependent functions including bacterial motility and biofilm formation (Lee et al, 2009), as well as the secretion of virulence-related enzymes such as lipases, proteases, elastases, and toxic metabolites such as pyocyanins (Loh et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Both activities are mainly due to the presence of polyphenols, the most abundant of which are the catechins, particularly epigallocatechin gallate (EGCG), which represents 50–80% of the total catechin content (Khan and Mukhtar, 2007). The reported antimicrobial activity of EGCG against human pathogens (Osterburg et al, 2009; Gordon and Wareham, 2010; Liu et al, 2017) may involve the direct disruption of bacterial membrane integrity (Lee et al, 2009), as well as indirect effects such as the chelation of iron (Hider et al, 2001), the inhibition of folate biosynthesis (Navarro-Martínez et al, 2005) and the inhibition of virulence functions such as type III secretion systems or quorum sensing (Spina et al, 2008; Yin et al, 2015; Tsou et al, 2017). In particular, interference with quorum sensing may affect density-dependent functions including bacterial motility and biofilm formation (Lee et al, 2009), as well as the secretion of virulence-related enzymes such as lipases, proteases, elastases, and toxic metabolites such as pyocyanins (Loh et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Catechins have strong anti-adipogenesis and anti-differentiation effects on mature adipocytes and 3T3-L1 preadipocytes via regulating the cyclic AMP/protein kinase A and C/EBPs/PPARγ/SREBP1C signaling pathways, which can thus exhibit the dual effect of preventing obesity and reducing fat [ 171 ]. Other than these, catechins also exhibit antimicrobial activities, as it has been reported that they can inhibit Salmonella enterica serovar Typhimurium type III protein secretion and invasion of host cells [ 172 ], syntaxin-1 expression [ 173 ], and induce endogenous oxidative stress in E. coli [ 174 ]. Catechin of green tea, EGCG, showed promising results in the inhibition of colon, prostate, lung, pancreatic, intestinal, and stomach cancers [ 158 ].…”
Section: Catechinsmentioning
confidence: 99%
“…Inhibitors of the internalization process will potentially be adhesion inhibitors and vice versa. EGCG ( Figure 21 ) has been shown to inhibit T3SS-mediated adhesion and internalization of multiple organisms including EPEC and EHEC, S. Typhimurium, and Y. pestis [ 251 , 252 ]. EGCG was analyzed for its ability to inhibit adherence of EPEC to human epithelial type 2 (Hep-2) cells.…”
Section: Inhibition Of Effectorsmentioning
confidence: 99%
“…They demonstrated that EGCG did not affect bacterial growth but was inhibiting SPI1 T3SS-dependent S . Typhimurium invasion of host cells [ 252 ].…”
Section: Inhibition Of Effectorsmentioning
confidence: 99%